“The Arab Spring” And Its Socio-Political and Economic Effects on North African Countries - Muhammadolim Muhammadsidiqov (Zien Journals, 2022)
This article analyzes the essence of the political, socio-economic processes taking place in the countries of North Africa, and the issues of influence on the internal and external policies of the countries of the region.
Keywords: political factor; jamahiriya; Middle East; North Africa